Health and suffering are associated with social support: a cross-sectional study of women and mothers with exhaustion and pain - Anja Gebhardt; Ann Langius-Eklöf; Susanne Andermo; Maria Arman (BMC, 2021)
Abstract Background Despite women are generally overrepresented in behavioral, mental, and musculoskeletal disorders, motherhood as a central part of women's life is poorly understood in relation to exhaustion and long-lasting pain. Mothers' health impairments imply suffering both for herself and her family. A profound understanding of health is needed taking mothers' subjective health experience, their suffering and life situation into account to give women, their families and society better prerequisites to alleviate exhaustion and long-lasting pain. The aim of the study was to describe health and suffering of women and mothers undergoing rehabilitation for long-lasting pain and exhaustion and its correlation with perceived social support. Methods The study had a cross-sectional design with an exploratory approach. A main sample consisted of 166 women undergoing rehabilitation for exhaustion and long-lasting pain and a reference sample included 129 women working and studying within health care professions. Both samples included women with and without children. Women's subjective health and suffering was assessed from a caring science perspective using the recently developed and validated Health and Suffering Scale. Two additional scales measuring exhaustion and social support were distributed among the two samples. Descriptive statistics and multiple linear regression models, including health and suffering and perceived social support, were analyzed. Results Mothers undergoing rehabilitation for pain and exhaustion reported significantly poorer health and more suffering compared to healthy mothers, but similar health and suffering when compared with childless women in rehabilitation. Health and suffering were correlated with perceived social support among both healthy and exhausted mothers. In both samples, the correlation between health and suffering and social support was stronger among mothers than among women without children. Conclusions Women and mothers living with exhaustion and long-lasting pain show signs of unbearable suffering and perceived insufficient social support. Social support from various sources particularly helps mothers to create meaning in life and make their suffering bearable. Hence, health care must address the fact that mothers are dependent on their immediate social environment and that this dependency interacts with their health and suffering on an existential level.